Development of Laser Range Finder Using 1550 nm Wavelength - Moloud Abufela, Basm Altaher (2006)
This thesis presents a design for measuring distance using infra light at 1550nm. A lot of experience has been gained in amplifying optical signal at 1550nm, however, another kind of range finder is being presented. The wavelength of 1550nm is selected because it is not harmful to the human eyes; it has less atmospheric absorption which makes it performs better in free space. A 1550 nm has less attenuation in free space than 902 nm or 1064 nm. 1550 nm is also safer than 902 nm and 1064 nm laser. In our system a 1550 nm, pulsed laser is used. Pulsed power is amplified by Erbium Doped Fiber Amplifier (EDFA), which is pumped by 1480nm, getting a 53.15mW 1550nm signal laser. A portion of the power after passing through the 1550 nm coupler triggers the counter to start the count. Optical pulse is collimated before it propagates in a free space. The receiver detects the laser power reflected from the target. The reflected amplified signal is used to stop the counter. The number of counts is proportional to time of flight. The resulting distance is calculated form the time of flight measured by the range finder. Since distance can be calculated this tends that, the velocity can be calculated. From the results, it is observed that the error is due to the time delay of the photodetector, and using EDFA gave an advantage of power control.